Urgensi Keterlibatan Orang Tua Dalam Pendidikan Anak di Jenjang Sekolah Dasar Pada Era Merdeka Belajar: Urgensi Keterlibatan Orang Tua Dalam Pendidikan Anak di Jenjang Sekolah Dasar Pada Era Merdeka Belajar - Nanditasari, Kadek Dwi; Basilius Redan Werang; Ni Putu Nita Loka; I Putu Arya Dimas Sugiarta Dhani; Kadek Dwi Prawira Utama; I Gede Reka Widiyantara (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2024)
The aim of this research is to obtain data on how involved parents are in their children's education at the elementary school level. This research method is descriptive quantitative with a survey research type. The research was carried out in elementary schools in the city of Buleleng Regency. The number of samples and population in this study were 43 parents of class VI students at SD N 1 Kaliuntu. The results of this research are based on survey results obtained in the aspect of mentors 65% in the good category, motivators 77% in the very good category, facilities 80% in the very good category, visits to schools 68% in the good category, discipline 95% in the very good category, use of gadgets 90% in the very good category good, communication 85% very good category, communication 85% very good category, nutrition and health 90% very good category. With this survey, it is recommended that parents improve aspects of guidance and visits to schools to achieve children's success and continue to maintain and improve all aspects that cause children to become successful and have character in the era of independent learning.